1985
DOI: 10.1071/ea9850027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of control of the sheep body louse (Damalinia ovis) on wool production and quality

Abstract: Groups of 35 Merino wethers under natural challenge by sheep body lice, Damalinia ovis, in south-western Queensland were subjected to four different chemical lice control treatments (arsenic, diazinon, cypermethrin and deltamethrin) over a 12-month period. Shearing took place in June. Louse populations were reduced by repeated treatments with cypermethrin. Despite high temperatures and some rainfall, populations in controls peaked at the end of summer, indicating that wool length influenced population growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 8 publications
3
11
1
Order By: Relevance
“…Cleland et al (1989) and James et al (2011) found no significant effect of lice on SS, but other studies have demonstrated some small negative effect. Niven and Pritchard (1985) reported sheep with moderate to heavy infestations produced less sound wool (1.7 vs 3.0 kg/head) and more cast wool (0.4 vs 0.1 kg/head) than sheep with few lice present. Several reports indicate lice have no effect on FD (Wilkinson et al, 1982;Niven and Pritchard, 1985;Cleland et al, 1989;James et al, 2011).…”
Section: Licementioning
confidence: 95%
“…Cleland et al (1989) and James et al (2011) found no significant effect of lice on SS, but other studies have demonstrated some small negative effect. Niven and Pritchard (1985) reported sheep with moderate to heavy infestations produced less sound wool (1.7 vs 3.0 kg/head) and more cast wool (0.4 vs 0.1 kg/head) than sheep with few lice present. Several reports indicate lice have no effect on FD (Wilkinson et al, 1982;Niven and Pritchard, 1985;Cleland et al, 1989;James et al, 2011).…”
Section: Licementioning
confidence: 95%
“…The data suggest that a positive correlation exists between the thickness of each region of the epidermis and the level of louse infestation (Table 1). Thus, although Britt et al (1985) established that epidermal thickness in louse-free adult Merino sheep does not vary significantly over a 12-month period, it is probable that any seasonal fluctuation in louse numbers [for example following shearing when the louse population is dramatically reduced (Niven and Pritchard 1985), or following treatment with insecticidal formulations] could result in an apparent seasonal variation to epidermal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The sheep biting louse, Bovicola ovis (Schrank) (Phthiraptera: Trichodectidae), is an ectoparasite of sheep in most parts of the world. Infestations cause economic losses by decreasing wool cut per head, reducing wool quality and causing cockle in sheep leather (Kettle & Lukies, 1982;Wilkinson et al, 1982;Niven & Pritchard, 1985;Heath et al, 1995). Historically, control of sheep lice has been mainly by insecticides.…”
Section: Introductionmentioning
confidence: 99%